REFORMASI SISTEM BIROKRASI DALAM PELAYANAN PERIZINAN DI PEMERINTAHAN KOTA KUPANG - William Djani; Maria Magdalena Lino (The Indonesian Journal of Public Administration (IJPA), 2020)
Abstract, This paper is intended to provide answers to some bureaucratic reform efforts related to systems and procedures in public services in Kupang City. Indonesia's public bureaucracy has undergone significant reform, which is a result of the convergence of external and internal factors in supporting change. Bureaucratic reform can be classified into three groups, namely institutional reform, apparatus resource reform and system and procedure reform. This review & review on the dimensions of Systems and procedures, which provide an evaluation of bureaucratic reforms carried out in the previous decade. The contents and spirit of bureaucratic reform reflect a new understanding of bureaucracy that is very different from the classical form of bureaucracy. As such, it has the potential to bring considerable change, not only in the role of the national public bureaucracy, but in the relations of systems and procedures. However, this study discusses the commitment of the Kupang City Government and the application of systems and procedures as a hindering factor in implementing effective bureaucratic reform.Keywords: Bureaucracy, System and procedure reform, Public Service. Abstrak, Tulisan ini dimaksudkan untuk memberikan jawaban atas beberapa upaya reformasi birokrasi terkait sistem dan prosedur dalam pelayanan publik di Kota kupang. Birokrasi publik Indonesia telah mengalami reformasi secara signifikan, yang merupakan hasil dari konvergensi faktor eksternal dan internal dalam mendukung perubahan. Reformasi birokrasi dapat diklasifikasikan menjadi tiga kelompok yaitu reformasi kelembagaan, reformasi sumberdaya aparatur dan reformasi sistem dan prosedur. Kajian & ulasan ini pada dimensi Sistem dan prosedur, yang memberikan evaluasi terhadap reformasi birokrasi yang dilakukan dalam dekade tahun sebelumnya. Isi dan semangat reformasi birokrasi mencerminkan pemahaman baru birokrasi yang sangat berbeda dari bentuk birokrasi klasik. Dengan demikian, memiliki potensi untuk membawa perubahan yang cukup besar, tidak hanya dalam peran birokrasi publik secara nasional, tetapi dalam hubungan Sistem dan prosedur. Namun demikian, kajian ini membahas komitmen Pemerintah Daerah Kota Kupang dan penerapan sistem dan prosedur sebagai faktor yang menghambat dalam pelaksanaan  reformasi birokrasi yang efektif.Kata kunci: Birokrasi, Reformasi Sistem dan prosedur, Pelayanan Publik